HEALTH PROFILE OF OLDER PERSONS IN A RESIDENTIAL HOME - kumniyom, nutda (วารสารพยาบาลศาสตร์และสุขภาพ, 2017)
This descriptive research explored health profile of elders resided in a residential home in the northeast of Thailand. There were 70 elders. Data were collected by using developed questionnaires and standard tools. Data were analyzed using descriptive statistics. Results, General information: Data showed that most of elders were females (51.4%); were in young old ages of 70-79 yrs. (42.9 %); were Buddhists (92.9%); were widows (52.9%); graduated from elementary schools (58.6%); had previous occupation as farmers (40.0%); resided in the home for 1-5 yrs. (55.1%); and had universal coverage insurance (78.6%). Physical health: Elders equally perceived their health at moderate and fair levels (31.4%), and perceived their health as better than others (45.7%). Nutritional status by using Body Mass Index, (BMI) indicated lower than standard levels (37.1%). There were 47.1% of elders with 2-5 diseases. Among those diseases were tuberculosis and cancer equally (82.9%). Mental status: Of 40% of elders had depression and 41.5% had dementia. Social health: Most of elders had good relationships with the home’s staffs (81.4%). The main source of money support was from donation (25.7%). Residential home staffs were the main caretakers for elders (81.4%). Of 37.1% of elders attended religious activities, while 32.9% attended social activities. Activities of daily living (ADL): Of 18.6% of elders had basic ADL dependency. Those who could not perform 5 instrumental ADLs ranged from 32.9% to 87.1%. Results of this study can be used as databases for research and for health and social service designs for elders residing in the home.